Peran Komunikasi Interpersonal dalam Meningkatkan Loyalitas Pelanggan: Studi Kuantitatif pada Industri Retail - Almadina Rakhmaniar (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to examine the role of interpersonal communication in increasing customer loyalty in the retail industry. The research method used is quantitative with data collection through questionnaires involving 100 respondents. The validity test results show that all research items are valid with a significance value of 0.000 <0.05. The reliability test resulted in a Cronbach's Alpha value of 0.768 which is greater than 0.700, so the instrument is declared reliable. The F test results show a calculated F value of 28.884, indicating that overall, the interpersonal communication quality variables have a significant influence on customer loyalty. The t test reveals that each independent variable has a calculated t value greater than the t table, indicating a significant effect of each variable on the dependent variable. The coefficient of determination (R Square) of 0.373 indicates that 37.3% of the variation in customer loyalty can be explained by the quality of interpersonal communication. The conclusion of this study is that interpersonal communication has a significant and positive influence on customer loyalty in the retail industry. This finding underscores the importance of effective interpersonal communication strategies in increasing customer loyalty. The results of this study can serve as a basis for developing better communication strategies in an effort to increase customer loyalty in the retail industry.